Balthus ou la quête de l'essentiel - Zeki, Semir; Balthus 1908-2001 (Les Belles Lettres [u.a.], 1995)
Item consists of a conversation between Semir Zeki and the artist.
Keywords: Balthus <1908- ...> - Interviews; Balthus <1908-2001>; Balthus <1908-2001> -- Interviews; Balthus -- 1908-2001; Artistes - Psychologie; Artists -- France -- Interviews; Interview; Frankreich